RNA interference technology : from basic science to drug development - Appasani, Krishnarao; Fire, Andrew; Nirenberg, Marshall (Cambridge University Press, 2005)
RNA Interference (RNAi) technology has rapidly become one of the key methods used in functional genomics. RNAi is used to block the expression of genes and create phenotypes that can potentially yield clues about the function of these genes. In the postgenomic era, the elucidation of the physiological function of genes has become the rate-limiting step in the quest to develop \'gene-based drugs\' and RNAi could potentially play a pivotal role in the validation of such novel drugs. In this cutting-edge overview, the basic concepts of RNAi biology are discussed, as well as the current and potential applications. Leading experts from both academia and industry have contributed to this invaluable reference for graduate students, post-docs and researchers from academia wanting to initiate RNAi research in their own labs, as well as for those working in research and development in biotech and pharmaceutical companies who need to understand this emerging technology. Forwarded by Andrew Fire, one of the winners of the 2006 Nobel Prize for the discovery of RNA Interference.
Keywords: RNA; Clinical Laboratory Techniques; GENETIKA BIOCHEMICKÁ; klinické laboratorní techniky; genetika, lékařská genetika